2015
DOI: 10.1002/jhm.2515
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital transfer patients discharged by academic hospitalists and general internists: Characteristics and outcomes

Abstract: BACKGROUND Prior work suggests inter-hospital transfer (IHT) may be a risky event. Outcomes for patients transferred from another acute care institution and discharged by hospitalists and general internists at academic health systems are not well described. OBJECTIVE Investigate the characteristics and outcomes of IHT patients compared with patients admitted from the emergency department (ED) to academic health systems. DESIGN Retrospective cohort study. SETTING/PATIENTS 885,392 adult inpatients discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
103
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 24 publications
10
103
1
Order By: Relevance
“…In a prospective study, adverse events were found to occur during interhospital transfer up to 30% of the time . Furthermore, patients subject to interhospital transfer have longer length of stay and higher inpatient mortality, even after adjusting for mortality risk predictors . Standardizing intrahospital handoff structures and communication practices has been shown to reduce medical errors .…”
mentioning
confidence: 99%
“…In a prospective study, adverse events were found to occur during interhospital transfer up to 30% of the time . Furthermore, patients subject to interhospital transfer have longer length of stay and higher inpatient mortality, even after adjusting for mortality risk predictors . Standardizing intrahospital handoff structures and communication practices has been shown to reduce medical errors .…”
mentioning
confidence: 99%
“…Furthermore, unlike discharges home or to sub–acute care facilities, also known to be error prone and lead to adverse events, in the case of IHT, patients are often more acutely ill and less stable. In fact, limited data suggest that aside from a select subset of patients requiring specialized care, individuals transferred may have increased resource utilization and greater‐than‐expected mortality than those who are not transferred . Moreover, these findings may not be entirely attributable to medical complexity among transferred patients.…”
mentioning
confidence: 99%
“…Today, the process of IHT varies tremendously across US hospitals, differences that may have significant implications for both cost and patient safety outcomes. Standardization of IHT, including patient selection and information exchange between transferring and accepting providers/institutions, is imperative to improve the quality and safety of this process.…”
mentioning
confidence: 99%
“…Transfer causes longer hospital stay and higher costs. For other surgical procedures, transfer imposes a higher risk of mortality, even when adjusted for patient mortality risk predictors . We found that about 15 children per year (0.12%) were transferred to another hospital, rather than discharged home.…”
Section: Discussionmentioning
confidence: 83%